Evaluation of the properties of tyre pyrolysis oils obtained in a conical spouted bed reactor. (1st June 2017) - Alvarez, J.; Lopez, G.; Amutio, M.; Mkhize, N.M.; Danon, B.; van der Gryp, P.; Görgens, J.F.; Bilbao, J.; Olazar, M.
Abstract: Waste truck tyre valorization by fast pyrolysis has been performed in a conical spouted bed reactor in the 425–575 °C range. The tyre pyrolysis oil (TPO) yield was found to decrease with increasing temperature whilst the yield of gas increased. The effect of temperature on TPO properties has been studied in order to establish the best possible valorization route. FTIR and chromatographic analysis revealed the presence of some undesired compounds with sulphur, nitrogen or oxygen functionalities (benzotiatholes, nitriles and carboxylic acids amongst others) and an increase of TPO aromaticity with increasing temperature. The carbon and sulphur content and the heating value of the TPO increased with temperature. The simulated distillation showed that approximately 70% of the TPOs produced at 425 and 475 °C correspond to diesel range, whereas that TPO obtained at 575 °C is between diesel and gasoline range. The properties of the TPOs evidenced their potential to substitute conventional fuels. However, some of them need to be improved, i.e., by reduction of the sulphur, nitrogen and aromatic content. Additionally, the TPO obtained at 425 and 475 °C could be an important source of limonene and that at 575 °C of xylenes, although current removal methods present some limitations. Graphical abstract: Highlights: The conical spouted bed reactor is suitable for truck tyre fast pyrolysis. The highest oil yields are attained between 425 and 475 °C (≈58 wt %). Tyre oil is a mixture of water, aromatic, aliphatic and heteroaromatic compounds. Limonene is the major compound with a maximum yield of 13.30 wt % at 475 °C. 425 and 475 °C oils share similarities with diesel and 575 °C one with gasoline.